1995
DOI: 10.1136/hrt.73.4.351
|View full text |Cite
|
Sign up to set email alerts
|

How do the clinical findings in patients with pericardial effusions influence the success of aspiration?

Abstract: The paucity of abnormal physical or echocardiographic signs of tamponade in breathless patients with pericardial effusion does not exclude symptomatic benefit being derived from pericardiocentesis. Pericardial aspiration is safe in appropriate hands, although aspiration of loculated effusions may not be as successful as aspiration of non-loculated effusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 12 publications
(10 reference statements)
0
22
0
Order By: Relevance
“…The presence of eVusion loculation reduces the likelihood of successful pericardiocentesis. 38 This study is based on the experience of a single centre and several operators were involved in performing the percutaneous procedures, although all were performed or supervised by experienced operators. A further limitation is the relatively short follow up, to date, of some of the patients with tuberculous pericarditis, in view of the fact that long term complications-particularly constrictive pericarditis-may only become evident many years after the original infection.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of eVusion loculation reduces the likelihood of successful pericardiocentesis. 38 This study is based on the experience of a single centre and several operators were involved in performing the percutaneous procedures, although all were performed or supervised by experienced operators. A further limitation is the relatively short follow up, to date, of some of the patients with tuberculous pericarditis, in view of the fact that long term complications-particularly constrictive pericarditis-may only become evident many years after the original infection.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, making an early diagnosis and having an experienced interventional cardiologist perform emergency pericardiocentesis are life-saving measures in cases of tamponade [4,5]. The present report describes an emergency response to a nearly catastrophic complication of PLAAC, wherein pericardial tamponade was reversed by aspiration of the pericardial hemorrhage, followed by immediate reinfusion of that blood.…”
Section: Discussionmentioning
confidence: 89%
“…This was confirmed by Krikorian and Hancock's study of 123 patients [33]: The procedure was successful in 93% of cases if the effusion was large and of both anterior and posterior location, whereas the rate of success was only 58% with small and posteriorly located effusions. Analyzing the predictors of failure in echocardiography-guided pericardiocentesis Cooper et al [56] observed that the only parameter associated with unsuccessful aspiration was loculation of pericardial effusion, particularly after cardiac surgery. However, in a recent large series of patients from the Mayo Clinic pericardiocentesis of loculated pericardial effusion after cardiac surgery, reached with echocardiographic guidance an efficacy of 96% with only 2% of major complications [49].…”
Section: Feasibility Of Fluoroscopy-guided Pericardiocentesismentioning
confidence: 99%